Penerapan Model Project Based Learning dalam Pembelajaran Keterampilan Menulis Teks Laporan Hasil Observasi Siswa Kelas X SMAN 20 Pangkep - Pebriansa; Nurhusna; Anita Candra Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the Project Based Learning (PjBL) model in teaching writing skills of observational report texts for grade X students of SMAN 20 Pangkep, to determine students' and teachers' perceptions of its implementation, and to identify obstacles that arise during the learning process. This study uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the implementation of PjBL takes place through six stages: determining basic questions, project planning, scheduling, monitoring, testing results, and reflection. The teacher acts as a facilitator who helps students work collaboratively to compile project-based observational report texts. Students show enthusiasm, creativity, and improved writing skills through direct observation activities, data processing, and report preparation. Teachers' and students' perceptions of PjBL are very positive because this model helps improve understanding of text structure, encourages collaboration, and makes learning more contextual. Obstacles found include students' difficulties in constructing coherent sentences, organizing observational data, and time constraints. Overall, PjBL is effectively implemented in teaching writing observational report texts because it is able to increase student engagement and literacy skills.